Test-retest reliability and agreement of the SPI-Questionnaire to detect symptoms of digital ischemia in elite volleyball players - van de Pol, D.; Zacharian, T.; Maas, M.; Kuijer, P. P. F. M. (Journal of Sports Sciences, 2017)
The Shoulder posterior circumflex humeral artery Pathology and digital Ischemia - questionnaire (SPI-Q) has been developed to enable periodic surveillance of elite volleyball players, who are at risk for digital ischemia. Prior to implementation, assessing reliability is mandatory. Therefore, the test-retest reliability and agreement of the SPI-Q were evaluated among the population at risk.